Bioremediation of heavy oily sludge: a microcosms study - Rondon-Afanador, Cinthya; Pinilla-Meza, Gustavo; Casallas-Cuervo, Francy C.; Diaz-Vanegas, Camila; Barreto-Gomez, Daniela; Benavides, Carolina; Buitrago, Nicole; Calvo, Melissa; Forero-Forero, Camila; Galvis-Ibarra, Valentina; Moscoso-Urdaneta, Victoria; Perdomo-Rengifo, Maria C.; et al. (Biodegradation (Dordrecht), 2023)
Oily sludge is a residue from the petroleum industry composed of a mixture of sand, water, metals, and high content of hydrocarbons (HCs). The heavy oily sludge used in this study originated from Colombian crude oil with high density and low American Petroleum Institute (API) gravity. The residual waste from heavy oil processing was subject to thermal and centrifugal extraction, resulting in heavy oily sludge with very high density and viscosity. Biodegradation of the total petroleum hydrocarbons (TPH) was tested in microcosms using several bioremediation approaches, including: biostimulation with bulking agents and nutrients, the surfactant Tween 80, and bioaugmentation. Select HC degrading bacteria were isolated based on their ability to grow and produce clear zones on different HCs. Degradation of TPH in the microcosms was monitored gravimetrically and with gas chromatography (GC). The TPH removal in all treatments ranged between 2 and 67%, regardless of the addition of microbial consortiums, amendments, or surfactants within the tested parameters. The results of this study demonstrated that bioremediation of heavy oily sludge presents greater challenges to achieve regulatory requirements. Additional physicochemical treatments analysis to remediate this recalcitrant material may be required to achieve a desirable degradation rate.